SYNTHESIS AND CHARACTERIZATION OF GRAPHITE NANOSTRUCTURE THIN FILM WITH SPUTTERING TECHNIQUE - Yunasfi Yunasfi; Salim Mustofa; Deswita Deswita (Jurnal Sains Materi Indonesia, 2011)
SYNTHESIS AND CHARACTERIZATION OF GRAPHITE NANOSTRUCTURE THIN FILM WITH SPUTTERING TECHNIQUE. Synthesis and characterization of graphite nanostructure thin film using the DC-sputtering technique has been carried out. Nanostructured graphite for target of deposition using DC-Sputtering technique has been prepared by milling technique using High Energy Milling (HEM) with the variation of milling time between 50 hours until 100 hours. First, the graphite target was prepared by doing a compaction using press machine to the nanostructured graphite powder got from milling process. Secondly, a thin filmof graphite was fabricated using DC-Sputtering technique. The phase identification of nanostructured graphite thin filmwere carried out using X-Ray Diffraction (XRD), and the surface and cross section morphology of thin filmwere observed using Scanning Electron Microscopy (SEM). XRD identification shows the presence of peaks of Si(100) and C(002) in all conditions of preparing powder using for target, but a shift of the angel‘s peak to the left and the decreasing of peak intensity were found. While the observation using SEM to surface morphology of thin film shows that the form of thin films are mostly homogeneous, smooth and flat at the milling time of 50-75 hours. From the SEM photograph of cross section, it is shown that there is a tendency of the more commonly found particles of droplets on the surface of thin film with the increasing of milling process against the carbon powder as a constituent of pellets for the DC-Sputtering targets, especially in the case of C/Si thin filmfabricated using target prepared by milling for 100 hours, the morphology of surface was worst.